Nature in Your Face – Disruptive Climate Change Communication and Eco-Visualization as Part of a Garden-Based Learning Approach Involving Primary School Children and Teachers in Co-creating the Future - Löfström, Erica; Klöckner, Christian A.; Nesvold, Ine H. (Frontiers in Psychology, 2020)
The paper describes an innovative structured workshop methodology in garden-based-learning (GBL) called “Nature In Your Face” (NIYF) aimed at provoking a change in citizens behavior and engagement as a consequence of the emotional activation in response to disruptive artistic messages. The methodology challenges the assumption that the change needed to meet the carbon targets can be reached with incremental, non-invasive behavior engineering techniques such as nudging or gamification. Instead, it explores the potential of disruptive communication to push citizens out of their comfort zones and into creative modes of re-creating futures. This is done by confronting us with consequences of consumption by means of art and eco-visualizations. The aim being to achieve awareness, mental flexibility, and spurring debate. Thus, we invite them to react – and act upon these reactions by communicating their feelings or thoughts. This is used as an entrance point for broader and/or deeper engagement in a structured three-step methodology; (1) Framing: A disruptive element is introduced into the local environment. This triggers an emotional reaction, which then is taken up in a process of framing the problem and working with solutions. (2) Twisting: in a guided process, the initial energy from the emotional confrontation is twisted into a creative exploration of innovative solutions, from the perspective of the children. (3) Using: The last stage is using the developed solutions in the local social system (or refining them further). The methodology is being applied in cooperation with a primary school, and is iteratively adjusted and evaluated in a formative, action-research based approach scenario. NIYF is to stimulate societal engagement through deliberately confronting stakeholders with unexpected and potentially upsetting appearances of nature, climate effects, or carbon-neutral lifestyle scenarios. We have verified the practical usefulness and potential of the methodology and found that NIYF triggers societal engagement and transition, negotiating responsibilities and unlocking action potentials. We also found that eco-anxiety, denial, self-efficacy and cognitive dissonance form childrens’ understanding of plastic. The project marks a paradigm shift from creating knowledge to using knowledge to create action, and a focus on learning from evaluating and adapting the approach in the field.